Scent of a Killer: Microbial Volatilome and Its Role in the Biological Control of Plant Pathogens - Tilocca, Bruno; Cao, Aocheng; Migheli, Quirico (Frontiers in Microbiology, 2020)
The use of synthetic fungicides represents the most common strategy to control plant pathogens. Excessive and/or long-term distribution of chemicals is responsible for increased level of environmental pollution, as well as adverse health consequences to human and animal. These issues are deeply influencing public perception, as reflected by the increasing demand for safer and eco-friendly agricultural commodities and their by-products. A steadily increasing number of research efforts is now devoted to explore the use of safer and innovative approaches to control plant pathogens. The use of microorganisms as biological control agents (BCAs) represents one of the most durable and promising strategies. Among the panoply of microbial mechanisms exerted by BCAs, the production of volatile organic compounds (VOCs) represents an intriguing issue, mostly exploitable in circumstances where a direct contact between the pathogen and its antagonist is not practicable. VOCs are potentially produced by all living microorganisms, and may be active in the biocontrol of phytopathogenic oomycetes, fungi and bacteria by means of antimicrobial activity and/or other cross-talk interactions. Their biological effects, the low hazard risk on both the environment and consumers, and the ease of application in different agricultural systems, make the use of VOCs a promising and sustainable approach to replace synthetic fungicides in the control of plant pathogens. In this review, we focus on VOCs produced by bacteria and fungi, and on their role in cross-relationship established with plant pathogens. The mutual effects of plant- and microbial-volatilome on the whole system biology of both BCAs and the plant host are also briefly reviewed.